An evaluation of LQR and fuzzy logic controllers for active suspension using half car model - Hasbullah, Faried; Faris, Waleed Fekry (Inderscience Enterprises Ltd, 2010)
The application of the linear quadratic regulator (LQR) and fuzzy logic controller (FLC) in the field of active vibration isolation for a vehicle suspension system is presented to overcome the limitation of passive suspension system and the performances of the two active controllers are compared with the passive system. Results show that the performance of the LQR controller is better than the FLC at the expense of control force. The performances of both active controllers are better than the passive system in terms of settling time.